Kandungan kimia kemenyan Sumatra Utara (Styrax benzoin) dan prospek pengembangannya: tinjauan literatur - Ridwansyah Ridwansyah; Titi Candra Sunarti; Khaswar Syamsu; Farah Fahma; Elisa Julianti (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
North Sumatra is the largest producer of incense (benzoin) in Indonesia and the world. There are 3 varieties of incense that have the potential to be developed. Indonesia has exported incense to Singapore, Malaysia, and China. Incense is exported in the form of raw materials, so the added value is minimal. In order to increase the added value of incense, it can be produced into incense extract. So far, extraction methods have been carried out using conventional methods, including maceration, boiling with water, and distillation with water vapor. The potential of incense has not been fully utilized, especially from its extraction method, so it still needs to be developed. This article aims to review and identify the chemical components of frankincense (Styrax benzoin) and its extraction methods. In addition, the prospects for product development from frankincense are also discussed. Incense extraction with Ultrasonification Assistant Extraction (UAE) is expected to increase the efficiency of the extraction process. The use of solvents and low temperatures, as well as a short extraction time, can maintain the quality of the incense extract. Incense extract can be applied as raw material for perfumes, pharmaceuticals, medicines, and nano applications such as anticancer and antibiofilm. The incense consists of some active ingredients such as cinnamic acid, benzoic acid esters (such as coniferyl cinnamate and cinnamyl), pinoresinol, -caumary benzoate, benzoic acid esters, and triterpenes. These active ingredients are applied as antibacterial and antioxidants. This literature review provides an overview of the characteristics of active ingredients in incense to expand its applications. Incense extract can be applied as a food additive, pharmaceutical, and health ingredient.